Myosin Va associates with mRNA in ribonucleoprotein particles present in myelinated peripheral axons and in the central nervous system. Issue 3 (27th January 2014) - Calliari, Aldo; Farías, Joaquina; Puppo, Agostina; Canclini, Lucía; Mercer, John A.; Munroe, David; Sotelo, José R.; Sotelo‐Silveira, José R.; Sotelo‐Silveira, José R.; Holt, Christine E.
ABSTRACT Sorting of specific mRNAs to particular cellular locations and regulation of their translation is an essential mechanism underlying cell polarization. The transport of RNAs by kinesins and dyneins has been clearly established in several cell models, including neurons in culture. A similar role appears to exist in higher eukaryotes for the myosins. Myosin Va (Myo5a) has been described as a component of ribonucleoprotein particles (RNPs) in the adult rat nervous system and associated to ZBP1 and ribosomes in ribosomal periaxoplasmic plaques (PARPs), making it a likely candidate for mediating some aspects of RNA transport in neurons. To test this hypothesis, we have characterized RNPs containing Myo5a in adult brains of rats and mice. Microarray analysis of RNAs co‐immunoprecipitated with Myo5a indicates that this motor may associate with a specific subpopulation of neuronal mRNAs. We found mRNAs encoding α‐synuclein and several proteins with functions in translation in these RNPs. Immunofluorescence analyses of RNPs showed apparent co‐localization of Myo5a with ribosomes, mRNA and RNA‐binding proteins in discrete structures present both in axons of neurons in culture and in myelinated fibers of medullary roots. Our data suggest that PARPs include RNPs bearing the mRNA coding for Myo5a and are equipped with kinesin and Myo5a molecular motors. In conclusion, we suggest that Myo5a is involved in mRNA trafficking both in the central and peripheral nervous systems. © 2013 Wiley Periodicals, Inc. Develop Neurobiol 74: 382–396, 2014